PERBANDINGAN SENSITIVITAS ETIS ACCOUNT OFFICER BANK UMUM KONVENSIONAL DAN BANK UMUM SYARIAH DI KOTA SURABAYA - Feby Riska Pradita (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The purpose of this research is to compare ethical sensitivity of account officer in conventional bank and sharia bank in Surabaya. This research is an empirical study using primary data collected from questionnaires. The data analysis used was T-test. The results of data analysis show that there is a different of ethical sensitivity between the account officer of conventional bank and sharia bank. This is because the factors affecting the individual ethical sensitivity, such as working environtment, necessities, behavior, and personal habbit are different.Keywords: Ethical sensitivity, Account officer, Conventional Bank, Sharia Bank.